1988
DOI: 10.1007/bf00542504
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of streptomycin in Ethiopian children with tuberculosis and of different nutritional status

Abstract: Fifty-six malnourished Ethiopian children with tuberculosis classified in four nutritional groups (normal, underweight, marasmus and kwashiorkor), were given streptomycin 20 or 30 mg.kg-1 i.m. The plasma concentration-time data revealed an increased apparent volume of distribution in children with kwashiorkor compared to normals. The total plasma clearance was low and did not differ between the nutritional groups. Thus, the half-life was prolonged only in kwashiorkor. The results could be explained by decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
16
1
Order By: Relevance
“…This was in contrast to a separate study that documented a significant decrease in the total CL and a corresponding significant increase in the t½ of penicillin in children with kwashiorkor only [47]. There was no influence of PEM on the total clearance of the three aminoglycoside antibiotics studied [41,48,50,52]. One of these studies involving streptomycin documented an increased plasma half-life in children with kwashiorkor but no change in children who were underweight or had marasmus only [48].…”
Section: Page 32 Of 52 European Journal Of Clinical Pharmacologycontrasting
confidence: 52%
See 4 more Smart Citations
“…This was in contrast to a separate study that documented a significant decrease in the total CL and a corresponding significant increase in the t½ of penicillin in children with kwashiorkor only [47]. There was no influence of PEM on the total clearance of the three aminoglycoside antibiotics studied [41,48,50,52]. One of these studies involving streptomycin documented an increased plasma half-life in children with kwashiorkor but no change in children who were underweight or had marasmus only [48].…”
Section: Page 32 Of 52 European Journal Of Clinical Pharmacologycontrasting
confidence: 52%
“…A separate study where the degree of malnutrition was undefined showed no effect of PEM on the Vd of theophylline [22]. In the case of streptomycin, children with kwashiorkor exhibited an increased Vd [48] whereas children with marasmus or underweight had a decreased Vd [48]. A decreased Vd for quinine in children with undefined PEM in one study [51] was in contrast to a separate study involving children with marasmus and marasmic-kwashiorkor where the Vd was unaffected [21].…”
Section: Protein Binding and Distributionmentioning
confidence: 53%
See 3 more Smart Citations